2022
DOI: 10.1093/biolinnean/blac071
|View full text |Cite
|
Sign up to set email alerts
|

Hand-Wing Index as a surrogate for dispersal ability: the case of the Emberizoidea (Aves: Passeriformes) radiation

Abstract: Measuring the dispersal ability of birds is particularly challenging and thus researchers have relied on the extended use of morphological proxies as surrogates for such ability. However, few studies have tested the relationship between morphological proxies and other dispersal-related traits. In this study, we test the relationship of the most commonly used morphological proxy for dispersal—the Hand-Wing Index (HWI)—with traits highly associated with dispersal abilities, such as geographic range size, migrato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
5
1
Order By: Relevance
“…We did not find an association between dispersal distances and geographic range size. Despite clear theoretical expectations and some empirical evidence (Alzate & Onstein, 2022;Arango et al, 2022;Capurucho et al, 2020;Laube et al, 2012;Lester et al, 2007), we found that natal dispersal distances of widespread species were similar to those of range-restricted species. A potential correlation between geographic range size and dispersal distances may be dampened by the negative correlation between dispersal distances and population size, as widespread species tend to be more abundant (Bock & Ricklefs, 1983;Brown & Munger, 1985) and less dispersive (Claramunt, 2021, this study).…”
Section: Discussioncontrasting
confidence: 98%
“…We did not find an association between dispersal distances and geographic range size. Despite clear theoretical expectations and some empirical evidence (Alzate & Onstein, 2022;Arango et al, 2022;Capurucho et al, 2020;Laube et al, 2012;Lester et al, 2007), we found that natal dispersal distances of widespread species were similar to those of range-restricted species. A potential correlation between geographic range size and dispersal distances may be dampened by the negative correlation between dispersal distances and population size, as widespread species tend to be more abundant (Bock & Ricklefs, 1983;Brown & Munger, 1985) and less dispersive (Claramunt, 2021, this study).…”
Section: Discussioncontrasting
confidence: 98%
“…Targeted searches along this river and in the intervening regions did not find populations of this species, supporting the hypothesis that this was a wandering individual (Ingels et al, 2012). Proxy measures like the HWI probably remain powerful predictors of dispersal potential generally, as evidenced in recent comparative (Arango et al, 2022;Claramunt, 2021;Dawideit et al, 2009;Sheard et al, 2020;Weeks et al, 2022) and experimental approaches (Naka et al, 2022) but may not be useful in all habitats or for all species, or when other historical or ecological variables (see for example Capurucho et al, 2020) overcome their effect. Many of these potential ecological variables, such as generation time and reproductive behaviour, are not available for many Amazonian species, highlighting the need for additional natural history data.…”
Section: Dispersal Ability and Gene Flowmentioning
confidence: 99%
“…Although a small effect, HWI tended to be negatively associated with range expansions. Previous work has identified HWI as being strongly positively correlated with dispersal ability across many bird taxa (Arango et al, 2022), meaning we would have expected to see more expansions as HWI increases. However, this effect may be confounded by the reproductive strategies of smaller birds with lower HWI.…”
Section: Discussionmentioning
confidence: 88%